2017
DOI: 10.3390/ijms18091982
|View full text |Cite
|
Sign up to set email alerts
|

Statin and Bisphosphonate Induce Starvation in Fast-Growing Cancer Cell Lines

Abstract: Statins and bisphosphonates are increasingly recognized as anti-cancer drugs, especially because of their cholesterol-lowering properties. However, these drugs act differently on various types of cancers. Thus, the aim of this study was to compare the effects of statins and bisphosphonates on the metabolism (NADP+/NADPH-relation) of highly proliferative tumor cell lines from different origins (PC-3 prostate carcinoma, MDA-MB-231 breast cancer, U-2 OS osteosarcoma) versus cells with a slower proliferation rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 108 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…At the same time, the enrichment of methylation-driven genes in “Statin pathway”, “Vitamin K metabolism” and “Metabolism” pathways also needs our attention. It has been reported that statins and their analogues can cause changes in the methylation levels of H3K27 and other genes in rapidly proliferating tumor cell lines ( 14 ). Vitamin K as a powerful redox-system, forms a bypass between mitochondrial complexes II and III, restores oxidative phosphorylation and aerobic glycolysis and it eliminates the hypoxic environment of cancer cells and induces cell death ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the enrichment of methylation-driven genes in “Statin pathway”, “Vitamin K metabolism” and “Metabolism” pathways also needs our attention. It has been reported that statins and their analogues can cause changes in the methylation levels of H3K27 and other genes in rapidly proliferating tumor cell lines ( 14 ). Vitamin K as a powerful redox-system, forms a bypass between mitochondrial complexes II and III, restores oxidative phosphorylation and aerobic glycolysis and it eliminates the hypoxic environment of cancer cells and induces cell death ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated in both normal and cancer cells (Iguchi et al, ; Mansouri, Mirzaei, Lage, Mousavi, & Elahian, ; Okamoto et al, ; Zhao et al, ). On contrary, it has been also demonstrated that treatment with ibandronate leads to increased cell cycle arrest in S phase in U‐2 osteosarcoma cells and in G2/M phase in MG‐63 osteoblast‐like cells (Karlic et al, ). In addition, Merrel et al showed that treatment with zoledronate increased the percentage of MDA‐MB‐231 cells in G1 phase (Merrell, Wakchoure, Lehenkari, Harris, & Selander, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that simvastatin inhibits the proliferation, migration, and invasion of PCa cells via the up-regulation of ANXA10 and inactivation of the AKT/PI3K pathway ( Miyazawa et al, 2017 ). Simvastatin can arrest the cell cycle at G1 in PC-3 cells through the AMPK pathway ( Karlic et al, 2017 ). In addition, lovastatin was found to enhance the efficacy of PRRA-TRAIL via the promotion of tumor suppression and induction of apoptosis ( Liu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%